Transformational leadership and educational management in four public education schools in Villa María del Triunfo. Lima - Abanto Castillo, Selene Consuelo (2023)
One of the trending topics in the educational field is both managerial and teacher leadership, and within the different types of leadership we consider that transformational leadership has a special influence on educational management and is the reason for our research, whose objective is to establish The relationship between transformational leadership and educational management in 4 schools in Lima. For this we use probabilistic samples from each of the schools and we use a quantitative approach in scientific research with a hypothetical deductive method, cross section and ordinal level. The data collection instruments, two questionnaires, were formed taking into account the validity criteria through three expert juries and the reliability through the Cronbach coefficient. Data analysis was performed using descriptive and inferential statistics for the hypothesis test, using Spearman's Rho. And it is basically found that there is a positive rating between transformational leadership and educational management, with a Spearman's Rho rating coefficient of 0.661. This value indicates a moderate to strong relationship between both variables. The two-sided significance is 0.000, which is less than the significance level set at 0.01. Therefore, it is evident that there is a significant relationship between transformational leadership and educational management in the educational institutions of Villa María del Triunfo, Lima.